Sketching a future for sociology and sociologists (A conference in memory of Natalia Panina and Myroslav Popovich) - Maksymenko, O. (Социология: теория, методы, маркетинг, 2019)
On 10 December 2018, the Institute of Sociology of the National Academy of Ukraine was proud to host an international conference in honour of two prominent figures in the field of philosophy and social sciences — Myroslav Popovich (1930-2018) and Natalia Panina (1949-2006). The theme of the conference, “The sociology of the future and the future of sociology in the 21st century”, was supposed to elicit views about what the future may have in store for this discipline, what sociology will be like in the century called by a perceptive scholar Yevhen Golovakha as early as 2001 a century of “escalating anthropogenesis”, what sociologists will soon have to deal with and what they should do in order to gain and retain a competitive edge.